FEASIBILITY TEST OF JACKFRUIT SEED FLOUR - Seni, Wildan; Samsuddin, Samsuddin; Kala, Pasyame Rambune (Transpublika Publisher, 2023)
Indonesia, being a tropical country, is home to a wide variety of plants, one of which is the jackfruit plant (Artocarpus heterophyllus Lamk). However, the utilization of jackfruit waste, particularly the seeds, still remains limited. With the increasing demand for food and advancements in technology, there is a growing interest in transforming jackfruit seeds into flour. In order to understand the nutritional value of jackfruit seed flour, researchers have conducted a proximate analysis on the flour. This analysis involved testing the levels of protein, carbohydrates, fat, and calories in the jackfruit seed flour using experimental design. The protein content was measured using the Kjeldahl method, carbohydrates were determined using the Deference method with Soklet, and fat and calories were calculated manually. The research findings revealed that the jackfruit seed flour contained 12.19 grams of protein, 56.21 grams of carbohydrates, 1.12 grams of fat, and a moisture content of 12.4 grams. These results highlight the potential of utilizing jackfruit seeds as flour, not only to reduce waste but also due to its high nutrient content.